2009
DOI: 10.1097/tp.0b013e31819a688a
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Renal Transplant Recipients Admitted to an Intensive Care Unit: A 10-Year Cohort Study

Abstract: The incidence of severe transplant-related complications requiring an admission to an ICU was at 16 of 1000 patients year with a mortality rate higher than the general ICU population (40% vs. 20%). These data suggest that immunosuppressive treatment of transplant patients with severe complications worsens significantly their outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 26 publications
7
36
2
11
Order By: Relevance
“…This finding is no different from other studies in this population, which report severe pulmonary complications more frequently after 6 months of transplantation, 8,9,16,18,23,24,27 although there are cases with different results. 17,28 Cardiogenic pulmonary edema is another condition often implicated in the genesis of ARF.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This finding is no different from other studies in this population, which report severe pulmonary complications more frequently after 6 months of transplantation, 8,9,16,18,23,24,27 although there are cases with different results. 17,28 Cardiogenic pulmonary edema is another condition often implicated in the genesis of ARF.…”
Section: Discussioncontrasting
confidence: 70%
“…7 Acute respiratory failure (ARF) is one of the most severe manifestations of pulmonary involvement, accounting for about half of hospitalizations in intensive care units (ICUs). [8][9][10] Bacterial and opportunistic infections are common causes of ARF, and are also factors associated with in-hospital mortality. 8 The epidemiological characteristics of ARF may be influenced by regional aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported varied rates of ICU admissions, ranging from 1% to 25%, 3 with discrepancies being attributed to differences in organization of surveillance between referring centers and transplant centers and individual policies regarding criteria for ICU admissions. 4 The donor population is also reflecting upward age trends, with more marginal kidneys and with associated comorbidities being included. In addition, as the age of transplant recipients is increasing with more associated comorbidities, the rate of ICU admissions may increase.…”
Section: Discussionmentioning
confidence: 99%
“…4,13 Sadaghdar and associates demonstrated that history of cardiac disease was the most frequent reason for immediate postoperative ICU admission among kidney transplant recipients, whereas sepsis was the 44 major reason for later ICU admissions. In addition, in line with our findings, they reported a better hospital outcome in the group 1 patients with a low mortality rate of 3.7% (0% in our study) and a short mean ICU stay of 5.1 days (3.7 days in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Sudden decrease in urine output may warrant surgical re-exploration [11]. Transplanted patients requiring prolonged mechanical ventilation postoperatively, have a worse outcome compared with patients who were extubated at the end of surgery [55]. Post-operative pain relief is essential after renal transplantation, as inadequately controlled pain can lead to agitation, tachycardia, hypertension and an increased risk of pulmonary complications.…”
Section: Postoperative Carementioning
confidence: 99%